TENTACLE COMPONENTS (NEMATOCYSTS AND ZOOXANTHELLA) OF Montipora danae in MARAK ISLAND, WEST SUMATERA - Lieng, Lieng; Zamani, Neviaty P.; Bengen, Dietriech Geoffrey; Naulita, Yuli (Asian Journal of Aquatic Sciences, 2024)
Coral animals have tentacles in which there are Nematocysts in the ectoderm layer and zooxanthella in the endoderm layer, and these two components have a role as a defense and food source; this study was conducted to identify the components of Montipora danae coral tentacles. The research was conducted in Marak Island, West Sumatra, with a purposive sampling method based on the presence of M.danae. The coral samples were decalcified to separate the tissue from the skeleton. The results of this study indicate that M.danae consists of Nematocysts type sH (small Holotrich), MpM-I (Microbasic p-Mastighopore I), and H (Holotrich). Holotrich has the highest relative abundance of 74-91%, MpM-I has 3,92-20,63% and sH has 3-24%. Holotrich has larger morphometrics than sH and MpM-I, namely 72,76-82,35 μm capsule length and 19,55-24 μm capsule width. The zooxanthella density of M. danae was lower than that of normal corals at 624 cells/cm2